El tratamiento de las unidades fraseológicas en la lexicografía bilingüe - Santamaría Pérez, María Isabel (ELUA: Estudios de Lingüística. Universidad de Alicante, 1998)
This study aims lo determine the treatment of the multiword lexical units in a bilingual Catalan-Spanish lexicography. The first part of this essay pays attention to the situation of nowadays' phraseology, observing both its theorical aspect and its usage in other disciplines such as the lexicography. The second part centers on the study of the fixed word combinations which appear in Catalan-Spanish dictionaries, especially those thought to be used in schools in order to find out the reasons why they were chosen if they appear in the macro o microestructure and if they use any kind of grammatical classification. Moreover we will focus over attention on the equivalences in the target language.